The origins, functioning and business model impact of the Sustainable Cotton Cluster in South Africa - Jordaan, Daniel du Plessis Scheepers (University of Pretoria, 2023)
Mini Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2023